Understanding and solving multistep arithmetic word problems - Nortvedt, Guri A. (NOMAD Nordic Studies in Mathematics Education, 2010)
This article discusses the findings of a study in which the interplay between reading, numeracy, and strategies for working on multistep arithmetic word problems was researched through two approaches. The first approach involved analysing results on national tests in reading and numeracy for a representative sample of 1,264 grade 8 (13-years-old) students. A scale of ten multistep arithmetic word problems was identified in the numeracy test. Proficiency in reading explained 44 % of the variance in scores on this scale, indicating a positive relationship between reading comprehension and success in word problem solving. The second approach involved analysing verbal protocol data for 19 grade 8 students who worked on a collection of multistep arithmetic word problems. Protocols consisted of both independent and scaffolded work. Interpretive analysis of student work on one of the eight word problems given in the protocol sessions revealed three main areas of difficulties: representing quantities in the word problem text, retrieving number facts from memory, and performing basic operations. Difficulties within more than one area were frequent. To students with below-average numeracy skills, executing the basic operations was the main obstacle for this particular word problem.